Enhancing organizational citizenship behavior using transformational leadership: Role of quality of work life - Heridiansyah, Jefri; Wahyudi, Wahyudi; Budiyono, Rokhmad; Setiyanti, Sri Wiranti (Edelweiss Applied Science and Technology, 2024)
In today’s dynamic landscape, organizations increasingly view organizational citizenship behavior (OCB) as a pivotal element in achieving their corporate objectives seamlessly. Effective leadership plays a critical role in shaping an organization’s capacity as a learning entity, fostering enhanced adaptability to change and elevating OCB levels. This study aims to explore the direct and indirect impacts of transformational leadership (TL) on OCB, with a specific focus on the mediating role of quality of work life (QWL). The research involved a sample of 200 respondents from diverse industries across Central Java, Indonesia. Data collection was conducted through questionnaires, and the results were analyzed using Structural Equation Modelling (SEM). The findings reveal a significant and positive direct relationship between TL, QWL, and OCB. Additionally, the study’s unique contribution lies in demonstrating that QWL serves as a partial mediator in the relationship between TL and OCB. The analysis underscores the importance of adopting transformational leadership approaches and introducing initiatives that enhance work-life balance to effectively boost OCB within organizations.